INTEGRATION OF ACCOUNTING INFORMATION SYSTEMS AND GOOD CORPORATE GOVERNANCE IN VILLAGE CREDIT INSTITUTION IN BALI - Saputra, Komang Adi Kurniawan (Faculty of Business, Widya Mandala Catholic University Surabaya, Indonesia, 2018)
This study aims to determine the effect of accounting information systems and good corporate governance on employee performance in Village Credit Institutions in Denpasar City. The data in this study are primary data obtained from distributing questionnaires directly to employees who work in Village Credit Institutions in Denpasar City. The sample in this study was 105 Village Credit Institutions using purposive sampling technique. The analytical method used is multiple linear regression. The results showed that the quality of accounting information systems and good corporate governance had a positive effect on employee performance. The results of the study simultaneously show that accounting information systems and good corporate governance have a significant effect on employee performance.